2 DOF resolution adjustment laser position sensor. (14th December 2009) - Shaik, Ahmed Asif; Tlale, Nkgatho Sylvester; Bright, Glen
A low cost sensor system is envisaged that has 2 distinct routes for resolution enhancement in position detection. The main area for application of the sensor design would be in the food processing and packaging industry where position resolution of the end effector is in the millimetre to sub-millimetre range. The sensor concept consists of a grid of laser light detectors attached to the stationary base and a grid of lasers attached to the mobile end effector. The photo detectors on the base provide one level for position detection enhancement, that is, the density of the sensor array. The second degree of freedom in improvement comes from the strategic positioning of a set of lasers attached to the end effector.